2009
DOI: 10.1111/j.1365-3040.2009.02043.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the dorso‐ventral organization of leaf structure and Kranz anatomy coordinate the control of photosynthesis and associated signalling at the whole leaf level in monocotyledonous species

Abstract: Photosynthesis and associated signalling are influenced by the dorso-ventral properties of leaves. The degree of adaxial/abaxial symmetry in stomatal numbers, photosynthetic regulation with respect to light orientation and the total section areas of the bundle sheath (BS) cells and the surrounding mesophyll (M) cells on the adaxial and abaxial sides of the vascular bundles were compared in two C4 [Zea mays (maize) and Paspalum dilatatum] and one C3 [Triticum turgidum (Durum wheat)] monocotyledonous species. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…All methods used were essentially as described previously (Soares et al , 2008; Soares-Cordeiro et al , 2009). Leaf samples were ground in liquid nitrogen and quartz sand.…”
Section: Methodsmentioning
confidence: 99%
“…All methods used were essentially as described previously (Soares et al , 2008; Soares-Cordeiro et al , 2009). Leaf samples were ground in liquid nitrogen and quartz sand.…”
Section: Methodsmentioning
confidence: 99%
“…The contact area between bundle sheath and mesophyll cells, indicated by S b , is related to the ability to transfer the metabolites that ensure the efficient operation of C4 photosynthesis (SoaresCordeiro et al, 2009). A higher value of S b indicates a more rapid metabolite transfer between bundle sheath and mesophyll (Sowiń ski et al, 2008;Soares-Cordeiro et al, 2009). Therefore, the contact area between bundle sheath and mesophyll cells was determined.…”
Section: Changes In Leaf Anatomical Structurementioning
confidence: 99%
“…This discrepancy might be caused by differences in the cultivars used and the level of N fertilizer administered. Soares‐Cordeiro et al () have also reported that P N of leaves of the C 4 grasses Paspalum dilatatum and Zea mays is higher with adaxial illumination, whereas that of the C 3 grass Triticum turgidum is the same with illumination of either leaf side.…”
Section: Discussionmentioning
confidence: 91%